Discovering dimensions of research ethics in doing oral history: going public in the case of the Ghent orphanages. (June 2020) - De Wilde, Lieselot; Roets, Griet; Vanobbergen, Bruno
In this article, we argue that research ethics in the doing of oral history research are inadequately addressed in the existing body of research. Although oral history researchers have paid considerable attention to procedural ethical issues, there is currently a lack of attention on situational research ethics in the doing of oral history. We address particular ethical challenges that we experienced while reconstructing the history of three remaining orphanages after the Second World War in the city of Ghent (a city in Flanders, the Dutch speaking part of Belgium) by drawing on oral history research from former orphans and ex-staff members. Their rather surprising, yet pertinent, questions enabled us to discover the political nature of research ethics, and prompted us to engage in 'going public'. We discuss the complexities of our attempt to provide a 'questionable' historical interpretation for the ambiguous history of these childhood institutions in the recent past.